2002
DOI: 10.1159/000064419
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Importance of Intestinal Hypermotility in NSAID-Induced Small Intestinal Damage in Rats

Abstract: Background/Aim: Nonsteroidal anti-inflammatory drugs (NSAIDs) such as indomethacin produce damage in the small intestine as a major adverse reaction. We examined the effect of various NSAIDs on intestinal motility and investigated the pathogenic importance of motility changes in the intestinal ulcerogenic response to indomethacin in rats. Methods: Animals without fasting were given various NSAIDs (indomethacin 10 mg/kg, diclofenac 40 mg/kg, flurbiprofen 20 mg/kg, naproxen 40 mg/kg) s.c., and in the case of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 25 publications
9
101
0
1
Order By: Relevance
“…Indeed, we showed that indomethacin at an ulcerogenic dose enhanced intestinal motility, the response that precedes the onset of intestinal damage as well as various pathogenic events such as enterobacterial invasion, neutrophil activation and iNOS expression (32,39). On the other hand, we confirmed our previous findings that dopamine and its agonist prevented indomethacin-induced small intestinal lesions in mice and these effects were antagonized by D 2 -receptor antagonists.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, we showed that indomethacin at an ulcerogenic dose enhanced intestinal motility, the response that precedes the onset of intestinal damage as well as various pathogenic events such as enterobacterial invasion, neutrophil activation and iNOS expression (32,39). On the other hand, we confirmed our previous findings that dopamine and its agonist prevented indomethacin-induced small intestinal lesions in mice and these effects were antagonized by D 2 -receptor antagonists.…”
Section: Discussionsupporting
confidence: 89%
“…The onset of these lesions was accompanied by the mucosal invasion of enterobacteria and the up-regulation of iNOS expression, those events being similarly observed after indomethacin treatment. We also confirmed that the ulcerogenic response induced by loxoprofen in the small intestine was significantly prevented by pretreatment of the animals with dmPGE 2 as a supplement for PG deficiency or ampicillin as an antibiotic, the same was reported using the intestinal indomethacin-induced intestinal lesions [3][4][5].…”
Section: Commentarysupporting
confidence: 84%
“…Several factors such as intestinal hypermotility, enterobacteria, neutrophils, nitric oxide (NO), and inducible NO synthase (iNOS) are involved in the pathogenesis of these intestinal lesions [3][4][5][6][7], yet a deficiency of endogenous prostaglandins (PGs) due to cyclooxygenase (COX) inhibition is most important in the background for the intestinal ulcerogenic response to NSAIDs [8][9][10]. Recent clinical studies, using capsule endoscopes or double-balloon endoscopes, confirmed that NSAIDs damage the small intestine in patients at a higher incidence than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the following has also been reported important in small bowel injury: the reduction of intestinal mucus due to NSAIDs, microcirculatory disturbances accompanying abnormally increased intestinal motility, NO derived from iNOS, inflammatory cytokines, neutrophil infiltration, and reactive oxygen species [26][27][28][29][30][31]. It is well that NSAIDs do not induce small-bowel injury in germ-free animals [20].…”
Section: Present Status Of Small Intestinal Mucosal Injury Caused By mentioning
confidence: 99%